Estructura del bosque y carbono almacenado en la biomasa de las especies forestales en bosque de terraza media del arboretum “el huayo”, Puerto Almendra, Iquitos, 2022 - Vela Ríos, Nibson Ney (2024)
The research was carried out at the “El Huayo” Arboretum of CIEFOR, Puerto Almendras. With the objective of determining its forest structure and carbon stored in the biomass of forest species of a mid-terrace forest. The results present a floristic composition of 566 trees, 33 families, 87 genera, 109 tree species, with DBH≥ 10cm. The familyLecythidacea and Fabacea (18.02% and 16.96% representation in the study area) are the ones with the greatest presence in plot VIII. There are 17 forest species most representative of 50% of the studied area, beingSchweilera coriacea, Pouroma tomentosa and Tachigalia bracteosumthose with the highest ecological importance value index (IVI). There is a total of 288369.89 Kg of aerial biomass, which represents 180231.18 Kg/ha and theEschweilera coriaceaIt has the greatest amount of biomass with 46815.03 Kg (29259.40 Kg/ha) and when quantifying 90.12 tC/ha, theEschweilera coriaceaIt has a greater amount of stored carbon with 23.41 tC (14.63 tC/ha) and when doing the Kruskal-Wallis test it statistically allowed us to accept the null hypothesis, that there is no difference in stored carbon in the structure of the forest according to forest species.